The complex multi-scale structure in simulated and observed emission maps of the proto-cluster cloud G0.253+0.016 ("the Brick") - Petkova, Maya A.; Kruijssen, Diederik; Kluge, Louise; Glover, Simon; Walker, Daniel L.; Longmore, Steven N.; Henshaw, Jonathan D.; Reißl, Stefan; Dale, James E. (Arxiv, 2021)
The Central Molecular Zone (CMZ; the central ~500 pc of the Milky Way) hosts molecular clouds in an extreme environment of strong shear, high gas pressure and density, and complex chemistry. G0.253+0.016, also known as `the Brick', is the densest, most compact and quiescent of these clouds. High-resolution observations with the Atacama Large Millimeter/submillimeter Array (ALMA) have revealed its complex, hierarchical structure. In this paper we compare the properties of recent hydrodynamical simulations of the Brick to those of the ALMA observations. To facilitate the comparison, we post-process the simulation and create synthetic ALMA maps of molecular line emission from eight molecules. We correlate the line emission maps to each other and to the mass column density, and find that HNCO is the best mass tracer of the eight emission lines. Additionally, we characterise the spatial structure of the observed and simulated cloud using the density probability distribution function (PDF), spatial power spectrum, fractal dimension, and moments of inertia. While we find good agreement between the observed and simulated data in terms of power spectra and fractal dimensions, there are key differences in terms of the density PDFs and moments of inertia, which we attribute to the omission of magnetic fields in the simulations. Models that include the external gravitational potential generated by the stars in the CMZ better reproduce the observed structure, highlighting that cloud structure in the CMZ results from the complex interplay between internal physics (turbulence, self-gravity, magnetic fields) and the impact of the extreme environment.
Gesehen am 29.09.2022